Piety, Purity, and Pain: The Head Shaving Ritual for Women in Ultra-Orthodox Communities and Its Underlying Concept of Halachah. - Brown, Iris (Modern Judaism: A Journal of Jewish Ideas & Experience, 2024)
Within the Hungarian and Galician Hasidic communities, women customarily shave their heads shortly before their weddings. Henceforth, they meticulously adhere to this practice, preserving a shorn appearance throughout the duration of their married lives. This practice has long stood at the center of a halachic and quasi-halachic discourse. An analysis of the arguments presented reveals that the halachic and kabbalistic foundations of this custom are extremely tenuous and largely dependent on homiletical interpretations. Although the precise origins of this practice remain elusive, its proponents have elevated its normative status, venerating it as an ancient and sacred tradition. This study endeavors to comprehend the underlying motivations driving the preservation efforts of this custom. The analysis herein demonstrates that the observance of this custom aligns three fundamentally non-halachic principles: a zealous commitment to minhag (custom); a "lust for asceticism," historically associated with select Hasidic groups since that movement's inception; and a demand for self-sacrifice, perceived as an ideal within greater ultra-Orthodox society. This study concludes that the normative standards emanating from these avowed non-halachic principles are regarded within ultra-conservative circles as an indispensable element of the Halachic system, thereby integrating these principles into their broader halachic worldview.